Cardiac-Specific Gene Editing via an AAV9-Tnnt2-SaCas9-miR122TS Vector - Luzi Yang; Congting Guo; Yueshen Sun; Yuxuan Guo (Bio-Protocol)
The adeno-associated virus serotype 9 (AAV9)-delivered gene expression driven by the cardiac troponin T (Tnnt2) promoter is broadly considered to be cardiac-specific. However, in cases where low AAV expression is sufficient to trigger a profound biological effect in CRISPR/Cas9 gene editing, the ectopic AAV9-Tnnt2 expression and gene editing in the liver becomes non-negligible. MicroRNA122 is a microRNA that is specifically expressed in the liver. The incorporation of the microRNA122 target sequence (miR122TS) into the 3' untranslated region (UTR) of the AAV transgene could reduce ectopic gene expression in the liver. Here, we provide a protocol for sgRNA design, plasmid construction, AAV packaging, and in vivo validation of a new AAV9-Tnnt2-SaCas9-miR122TS vector using publicly available materials and tools. The application of this new vector enables cardiac-specific gene editing while circumventing leakages in the liver.